Analysis on the Factors that Influence the Investment on Online Crypto Games - Culannay, Roger Charles (International Journal of Arts, Sciences and Education, 2022)
ABSTRACT: This study accentuated the common factors that influenced the investment on online crypto games among the 20 crypto players. The data collected were thoroughly analyzed using Thematic Analysis and have made clarified using Descriptive Survey in which it gathers the perception of the players regarding the factors that affected or influenced them in investing to Online Crypto game. The results dominantly show positive response of participants investing in crypto games with certain factors: for entertainment and money or income that they gained while playing.